A simple score for predicting urinary fistula in patients with renal hydatid cysts. Issue 1 (31st December 2022) - Chaker, Kays; Nouira, Yassine; Ouanes, Yassine; Bibi, Mokhtar
ABSTRACT: Hydatid cyst is a major health problem in developing countries. The kidney is in third position of organs affected by hydatid cyst. One of the complications of renal hydatid cyst is a urinary fistula. The purpose of this study is to identify preoperative predictive factors of urinary fistula in renal hydatid cyst and to develop a scoring system for this disorder. We retrospectively analyzed all patients operated for renal hydatid cysts between January 2000 and December 2020. We divided our patients into two groups according to whether or not the renal hydatid cysts opened in the urinary tract. Predictive factors of the presence of a urinary fistula have been studied to obtain a simple score to predict the presence of a urinary fistula. Differences were considered significant if p < 0.05. Urinary fistula was detected in 33 of 96 patients. Univariate analyses showed significant differences in patient age, cyst size, location, hydaturia, eosinophil count, and platelet count between patients with and without urinary fistula. In multivariate analyses, hydaturia (p < 0.005), eosinophil count >500/mm 3, (p = 0.01), cyst diameter >5 cm (p = 0.02), and upper or lower renal pole location (p = 0.003) were significant and independent predictors of urinary fistula. A score was developed to predict the opening of the cyst in the urinary tract. The total score varies between 0 and 15. The resulting area under the receiver operator characteristic curve was 0.798 (95% CI, 0.726–0.866; p = 0.023). At a cutoff point ≥8, the specificity achieved was 100%. Preoperative detection and management of urinary fistula are important issues in the treatment of renal hydatid cyst. Developing a scoring system based on routinely measured laboratory and radiologic factors will help the clinician to manage patients with renal hydatid cysts. External studies are needed to validate this new scoring system in routine clinical practice.